Evaluation of environmental compliance with solid waste management practices from mining activities : a case study of Marula Platinum Mine - Manyekwane, Dikeledi, Lethabo (My University, 2019)
Global production of Platinum Group Metals (PGMs) is dominated by South Africa due to its large economic resources base in the Bushveld Igneous Complex (BIC). PGMs are used in a wide range of high technology applications worldwide including medicinal, industrial and commercial purposes, and its contribution to the Gross Domestic Product (GDP) and creating jobs for many. In an area where mining activities dominate, there are likely to be problems that need effective environmental management approaches, which can be facilitated through legislations. Marula Platinum Mine (MPM) is located in Limpopo province BIC which has the second largest number of mining productivity in South Africa. Environmental legislations have been put in place by the South African government in order to avoid or minimise the footprints caused by PGM mining. This study looked at environmental compliance with solid waste management practices by Marula Platinum Mine (MPM) as guided by Mineral and Petroleum and Resource Development Act (MPRDA) and National Environmental Management Act (NEMA) as well as the environmental impacts of MPM in the surrounding communities. Both primary (questionnaires, field observations and key informant interviews) and secondary (NEMA, MPRDA, journals, reports, pamphlets, internet and books) data was used to address the objectives of the study. Descriptive method and Statistical Package for Social Sciences (SPSS) version 25 were used for the analysis of data. The key research results revealed that MPM was compliant with 65% and 21% partially compliant with solid waste management practices. Only 14% of information on solid waste management practices could not be accessed because MPM is still operational. MPM had also had negative footprints on the surrounding villages such as dust generation and cracks on walls and floors on houses of community members, strikes and increase in the usage of substance abuse. Recommendations of the study are that MPM should address challenges that hinder environmental compliance so as to be 100% compliant with MPRDA and NEMA regulations. MPM should also provide other mitigation measures for blasting of explosives to reduce dust generation and problems of cracks on houses of surrounding village members.
Thesis (M. Sc.(Geography)) -- University of Limpopo, 2019
Keywords: Environmental compliance; environmental management; Platinum group metals (PGMs); Marula Platinum Mine (MPM); Bushveld Igneous Complex (BIC); National Environmental Management Act (NEMA); Mineral resource Development Act (MPRDA); Environmental management performance Assessment Report (EMPAR); Solid waste management; Air -- Pollution -- Standards -- South Africa; Environmental toxicology; Pollution -- South Africa; Integrated solid waste management